2008
DOI: 10.2109/jcersj2.116.163
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature synthesis of biomorphic cellular SiC ceramics from wood by using a Na flux

Abstract: Wood from balsa and Japanese cypress was transformed into carbonaceous preforms by pyrolysis and subsequently converted into cellular SiC ceramics by heating with Na and Si at 973 K for 86.4 ks. X-ray diffraction showed the structure of the formed SiC to be cubic b-type. Cellular structures similar to those of the preforms were observed for the resulting porous SiC ceramics by scanning electron microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…No phase diagram has been reported for the Na-Si binary system. However, as discussed in the previous reports, 17,18) some amount of Si is considered to be dissolved in a Na melt.…”
Section: Low-temperature Synthesis Of Sic Porous Granules With a Na Fluxmentioning
confidence: 98%
See 1 more Smart Citation
“…No phase diagram has been reported for the Na-Si binary system. However, as discussed in the previous reports, 17,18) some amount of Si is considered to be dissolved in a Na melt.…”
Section: Low-temperature Synthesis Of Sic Porous Granules With a Na Fluxmentioning
confidence: 98%
“…Recently, we found that -type cubic SiC could be prepared from a Si and fullerene powder mixture or a Si and amorphous carbon (carbon black) powder mixture by the Na flux method at 900-1000 K. 16,17) Furthermore, woods from balsa and Japanese cypress were transformed into carbonaceous preforms by pyrolysis and subsequently converted into cellular SiC ceramics by heating with Na and Si at 973 K. 18) Cellular structures similar to those of the preforms were observed for the resulting porous SiC ceramics. However, these SiC pellets and cellular SiC could not have the adequate strength and stiffness because of their low density.…”
Section: Introductionmentioning
confidence: 99%
“…After formation of SiC with Na vapor and Na evaporation from the sample, residual carbon was removed as CO2 by heating the product in air. Figure 12 shows a photograph and a scanning electron micrograph of the β-SiC bulk prepared by heating carbonized balsa wood with Si and Na at 973 K for 24 h. 46) The as-prepared sample was covered with Na which was removed by reaction with alcohol. The structure and texture of the original carbonized wood were well maintained.…”
Section: Jcs-japanmentioning
confidence: 99%
“…1) In 2006, synthesis of new ternary carbides was attempted by using a Na flux. During this study, it was revealed that the Na flux was effective for the low-temperature synthesis of SiC 2) 4) ahead of the preparation of a new ternary carbide, Ba 3 Si 4 C 2 .…”
Section: Introductionmentioning
confidence: 99%